Chemical Composition, Crystal Structure, and Microstructure of Slags on the Korean Peninsula from the First Copper Production Remains of the 9th Century - Choi, Hyoryeong; Yu, Yeongchun; Cho, Namchul (Crystals (Basel), 2024)
The scarcity of excavated early-stage smelting sites related to copper production presents significant challenges in gaining a comprehensive understanding of the copper production process. However, the archaeological site discovered in 2018 in Daeryang-ri, Jinan-gun, Jeollabuk-do, boasts a substantial number of copper smelting remains and related slags, marking it as the first copper manufacturing production site identified on the Korean Peninsula. Consequently, this study selected 10 slag samples, chosen based on surface color and characteristics indicative of a connection to copper smelting, for scientific analysis to accurately ascertain the site’s nature. The primary component analysis of the slags indicated that CuO content ranged from 0.30 to 3.29 wt%, which, although not high, reveals significant quantities of FeO and SiO2. X-ray diffraction analysis revealed the presence of minerals such as cristobalite, along with fayalite and wüstite, commonly found in slags, varying by sample. Furthermore, microstructural observation revealed circular copper particles containing sulfur and iron, indicating the presence of copper particles in a matte state that have not been refined. This analysis suggests that the slags recovered from Jinan Daeryang-ri bear evidence of iron smelting at the site, with the slag being produced as an intermediate by-product during copper production.